2023
DOI: 10.1523/jneurosci.0237-23.2023
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cells Are Heterogeneous in Different Brain Regions and Are Dramatically Altered in Alzheimer's Disease

Abstract: Vascular endothelial cells play an important role in maintaining brain health, but their contribution to Alzheimer’s disease (AD) is obscured by limited understanding of the cellular heterogeneity in normal aged brain and in disease. To address this, we performed single nucleus RNAseq on tissue from 32 human AD and non-AD donors (19 female, 13 male) each with five cortical regions: entorhinal cortex, inferior temporal gyrus, prefrontal cortex, visual association cortex and primary visual cortex. Analysis of 51… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 68 publications
(90 reference statements)
0
10
1
Order By: Relevance
“…This provides important evidence for the evolutionary-unique, human-specific role of BEC and cerebrovasculature in brain neuroimmunity in AD and justifies efforts of antineuroinflammatory drug candidate screening in BEC. Simultaneously, disease-associated neuroinflammation has been shown to contribute to BBB dysfunction in AD, ,, and a single nucleus transcriptomic analysis of AD patients’ brain revealed the upregulation of genes related to immune responses and cytokine secretion in BEC, all suggesting that reducing inflammation in BEC could prove therapeutically useful in AD.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…This provides important evidence for the evolutionary-unique, human-specific role of BEC and cerebrovasculature in brain neuroimmunity in AD and justifies efforts of antineuroinflammatory drug candidate screening in BEC. Simultaneously, disease-associated neuroinflammation has been shown to contribute to BBB dysfunction in AD, ,, and a single nucleus transcriptomic analysis of AD patients’ brain revealed the upregulation of genes related to immune responses and cytokine secretion in BEC, all suggesting that reducing inflammation in BEC could prove therapeutically useful in AD.…”
Section: Discussioncontrasting
confidence: 54%
“…Interestingly, as opposed to BEC isolated from the AD patient’s brain, in our model, we did not observe vast differences in the expression of inflammatory marker genes in AD iBEC as compared to control iBEC, suggesting a lack of a strong disease-associated inflammatory phenotype in those AD cells in vitro. Intriguingly, recently reported transcriptomic analysis demonstrated striking molecular heterogeneity of human BEC found in different brain regions, distinct segments of the arteriovenous axis and disease stages, also in relation to immune responses. ,, Therefore, it is possible that our AD hiPSC-derived iBEC could represent the BEC subpopulation with only a moderately altered immune profile in AD, highlighting the complexity of BBB neuroinflammation in AD.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…While here, we focused on brain myeloid cells, our parent study included snRNA-seq of all brain cell types. We found that microglia are relatively uniform across the neocortex, whereas astrocytes and endothelial cells have brain region-specific signatures [ 6 , 46 ]. Astrocytes develop an apparent decreased activation (“burnt out”) phenotype in end-stage disease [ 46 ], whereas we see no evidence of an analogous state for microglia.…”
Section: Discussionmentioning
confidence: 99%